PRESSURE FLOTATION METHOD. THE ESTIMATED ASSESSMENT OF THE SIZE AND SHAPE OF RECOVERABLE FINES OF PRECIOUS METALS - A. V. Sankin (Современная наука и инновации)
The process of extracting fines of precious metals by the method of pressure flotation is considered in the paper. Estimated calculations of the size and mass of the raised from the dumps gold fines were made. The author gives the conclusions that allow to determine the application of the pressure flotation method depending on the used raw materials containing fine gold fractions.